BERITA PADA BLOG SOSIAL (ANALISIS ISI TERHADAP BERITA HUKUM PADA KOMPASIANA PERIODE JANUARI - OKTOBER 2012) - , Christiany Juditha; , Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Social blog is one of the journalism media currently used by ordinary citizens to express their aspirations. It starts from simply as a writing hobby up to serious writing to promote democracy and strengthen the freedom of information. Yet, the content of the products generated by citizen journalism still face the issues of quality and ethics which are often violated by the citizen journalists. As the largest social blog in Indonesia and Asia, Kompasiana also practices citizen journalism. It produces hundreds of posts every day including news written by ordinary citizens but read and taken as references by a lot of people. It is interesting to study how to present law news in Kompasiana social blog from January to October 2012? The purpose is to see the news production at this social blog in terms of quality and ethics of citizen journalism. The method used is quantitative content analysis. The results showed that characteristics of law news on Kompasiana social blog are generally concise, conversational and easily read and understood though only little news provides hyperlinks, as additional information for the readers. Interaction between kompasianer (news writer) and the readers also takes place with many comments in the news. This means that strengthening freedom of information and expressions and democratic process also take place. However, there are few comments that often attack those who involve in a reported case not objectively. Criticism and differences of opinion about certain news also occur leading to misunderstandings and ends in conflicts and comment war among them. Citizen journalism ethics which are likely to be violated by the citizen journalist is quoting other peopleâs work without mentioning source. Besides, they also do not write down the source of the law violation obtained. Yet, both ethic violations are relatively very few.